Analysis of Deixis in “An Irish Goodbye” Short Film - Faradiba Sari Harahap (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
The objective of the research is to analyze the types, and the dominant type of deixis used in “An Irish Goodbye” short film script. In completing the analysis, this research uses qualitative research method. In data collection technique, the researcher uses document analysis. This research used set of words or film script as the data in the forms of monologues delivered by Alex, an Irish man, as the main character taken from “An Irish Goodbye” short film directed by Cody Farren.  There are five types of deixis are focused to be analyzed in this research. All the types of deixis covering personal pronoun, social, discourse, place, and time deictic expressions as in Levinson (1983) are found in the “An Irish Goodbye” short film script. In person deixis, the deictic expression found are personal pronoun. The results of the research indicates that (1) there are 273 data of five deixis types found on “An Irish Goodbye” short film script, consisting of: 80 data (29.30%) of person deixis, 21 data (7.70%) of spatial deixis, 131 data (47.99%) of temporal deixis, 33 word (12.08%) of social deixis, and 8 data (2.93%) of discourse deixis. Hence, the temporal deixis (131 deictic words or 47.99%) is the most frequently used deixis.